Risk factors of ischemic stroke and their interconnection - Mishchenko, Marina Mikhailovna; Shevchenko, Alexander Sergeevich; Mishchenko, Alexander Nikolaevich (Perfect Publishing, 2020)
Cardiovascular disease is the leading cause of premature death. In turn, among cardiovascular diseases, the leader is ischemic stroke. The main risk factors for ischemic strokes (behavioral, physiological, genetic, environmental) act synergistically and are pathogenetically interconnected.
Keywords: cardiovascular diseases; ischemic stroke; risk factors; age factor; hypodynamia; hypercholesterolemia; hyperglycemia; diabetes; obesity; overeating; salt; alcohol; tobacco smoking; arterial hypertension; atrial fibrillation; vascular atherosclerosis; environmental burden